Analysis of Factors Affecting Purchase Intention to Use: A Study on The Swoop Transportation Application - Lazuardi, Tazqia Nabila; Syah, Tantri Yanuar Rahmat (Universitas Mercu Buana, 2024)
This study investigates the factors influencing purchase intentions for environmentally friendly online transportation services, focusing on Environmental Concern, Perceived Service Value, Brand Familiarity, and Willingness to Pay. By analyzing these elements, the research aims to understand their role in fostering sustained interest and using eco-friendly transportation options. Utilizing an exploratory approach, we surveyed customers familiar with or who have utilized environmentally friendly transportation in the Jabodetabek area. Our target population includes employees who engage with these services. The findings are anticipated to contribute to marketing management theories by offering insights into consumer behavior related to sustainable purchasing. Data were collected through an online questionnaire, employing convenient sampling to select respondents. Statistical analysis was conducted using SPSS and Lisrel for structural equation modeling (SEM). Results reveal significant relationships among environmental friendliness, perceived value, brand familiarity, ongoing purchase intentions, and the willingness to pay a premium. This research highlights the application of signaling theory in the context of environmental sustainability, providing valuable insights into how customer perceptions of value drive their intentions to engage with eco-friendly transportation services. These findings can inform effective marketing strategies for promoting sustainable transportation solutions.